2007
DOI: 10.1107/s160053680700534x
|View full text |Cite
|
Sign up to set email alerts
|

4-(Bromomethyl)benzophenone

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean (C-C) = 0.003 Å R factor = 0.033 wR factor = 0.097 Data-to-parameter ratio = 19.0 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The title compound, (I), is an important intermediate for the synthesis of water-soluble photoinitiators (Green & Green, 1998). Previously, we have reported the crystal structure of 4-(bromomethyl)benzophenone (Xu et al, 2007). Now we report here the crystal structure of 4-(chloromethyl)benzophenone, (I).…”
Section: Data Collectionmentioning
confidence: 78%
See 2 more Smart Citations
“…The title compound, (I), is an important intermediate for the synthesis of water-soluble photoinitiators (Green & Green, 1998). Previously, we have reported the crystal structure of 4-(bromomethyl)benzophenone (Xu et al, 2007). Now we report here the crystal structure of 4-(chloromethyl)benzophenone, (I).…”
Section: Data Collectionmentioning
confidence: 78%
“…1) is non-planar: the dihedral angle between the C2-C7 benzene ring and the C9-C14 phenyl ring is 58.10 (8)°. The corresponding angle in the bromo analogue is 59.53 (6)° (Xu et al, 2007). The carbonyl group is twisted from the C2-C7 and C9-C14 planes by 29.13 (11) and 28.87 (11)°, respectively.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative contributions of different interactions to the Hirshfeld surface calculated for ( 1 ), ( 2 ), MEJPIB as well as a few related chlorophenyl and bromophenyl derivatives ( S hibakami and Sekiya, 1995; Ronaldson et al , 2005; Xu et al , 2007; Gowda et al , 2009) retrieved from the CSD are shown in Figure 8. It should be noted that the contribution of H···Cl contacts (14.8%) to the Hirshfeld surface area in ( 1 ) is comparable to that of H···O contacts (13.2%), which include both N–H···O and C–H···O interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The relative contributions of different interactions to the Hirshfeld surface calculated for (1), (2), MEJPIB as well as a few related chlorophenyl and bromophenyl derivatives (Shibakami and Sekiya, 1995;Ronaldson et al, 2005;Xu et al, 2007;Gowda et al, 2009)…”
Section: A Crystal and Molecular Structurementioning
confidence: 99%